1992
DOI: 10.2337/diacare.15.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Health Status in Diabetic Patients: Diabetes Impact Measurement Scales

Abstract: The Diabetes Impact Management Scales (DIMS) is an easily administered questionnaire with internal consistency and test-retest reliability. Preliminary correlative analyses support the validity of the instrument as a measure of health status in adult type I and type II diabetic patients. Further work will be necessary to firmly establish the validity of the DIMS and its usefulness in clinical outcomes research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 7 publications
0
42
0
1
Order By: Relevance
“…The need to assess QOL in various diseases led to the development of disease-specific instruments [6,7,8,9]. Survey instruments for HRQOL in kidney disease have been successfully used in dialysis patients and have shown adequate validity (i.e., they measure what they were intended to measure), reliability (i.e., their results are consistent, or remain similar under stable conditions), responsiveness (i.e., a change in the observed score reflects a true change in patient’s condition), and sensitivity (the ability to reflect true changes or differences when such changes exist) [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The need to assess QOL in various diseases led to the development of disease-specific instruments [6,7,8,9]. Survey instruments for HRQOL in kidney disease have been successfully used in dialysis patients and have shown adequate validity (i.e., they measure what they were intended to measure), reliability (i.e., their results are consistent, or remain similar under stable conditions), responsiveness (i.e., a change in the observed score reflects a true change in patient’s condition), and sensitivity (the ability to reflect true changes or differences when such changes exist) [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The DIMS includes 44 items measuring four scales, with a higher score representing a better HRQOL. A previous validation study of the DIMS indicated high internal consistency for all scales, good test-retest reliability, and good patient-clinician agreement [8].…”
Section: Introductionmentioning
confidence: 68%
“…For ADDQoL, there were 12 interviews (19), for D-39 an unknown number of interviews with patients (7) and for DIMS and DCP no conversations with a patient were mentioned (14,21). We did not find any qualitative research with international design in the development of a DR-QoL instrument.…”
Section: Main Findingsmentioning
confidence: 98%
“…During the past few decades, considerable effort has been devoted to the study of patients' self-management behaviours and adherence to the treatment. In DR-QoL research, questionnaires that are in use are listed in Appendix 1 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). ATT39, PAID, DDS, the QSD-R, DHP, ADS, and ADDQoL are focused only on some aspects such as diabetes-related distress or additionally on the activity or the eating behaviour.…”
Section: Introductionmentioning
confidence: 99%